1994
DOI: 10.1288/00005537-199408000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐8 expression in otitis media

Abstract: Based on recent studies in the authors' laboratory on the correlation of cytokines and inflammation in otitis media (OM), the authors hypothesized that in chronic otitis media with effusion (COME) interleukin-8 (IL-8) is responsible for 1. the accumulation of leukocytes in the middle ear cleft and 2. in situ leukocyte activation with subsequent tissue damage. Additionally, the authors hypothesized that IL-8 expression is at least in part under the control of interleukin-1 (IL-1) and tumor necrosis factor (TNF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
69
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 18 publications
7
69
1
Order By: Relevance
“…These mucins vary in size and can be membrane bound or secreted. The process of defining the specific functions of each of these mucin products in the middle ear is still ongoing.There is currently a growing body of evidence demonstrating that a cytokine mediated inflammatory response is important in the pathophysiology of acute and chronic otitis media [8][9][10][11][12][13][14][15]. This study, along with similar studies conducted in our laboratory using chinchilla middle ear epithelial cells, shows clear evidence of this cytokine mediated inflammatory response particularly as it relates to mucin pathophysiology and regulation.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…These mucins vary in size and can be membrane bound or secreted. The process of defining the specific functions of each of these mucin products in the middle ear is still ongoing.There is currently a growing body of evidence demonstrating that a cytokine mediated inflammatory response is important in the pathophysiology of acute and chronic otitis media [8][9][10][11][12][13][14][15]. This study, along with similar studies conducted in our laboratory using chinchilla middle ear epithelial cells, shows clear evidence of this cytokine mediated inflammatory response particularly as it relates to mucin pathophysiology and regulation.…”
mentioning
confidence: 54%
“…Several cytokines have been found in a high percentage of these effusions, including TNF-α and IL -1β [6]. In addition to the general inflammatory regulatory mechanisms associated with these cytokines evidence exists that TNF-α and IL-1β are also integral in the inflammatory response in otitis media and regulate mucin production and secretion from middle ear epithelium [7][8][9][10][11]. Previous investigations in our laboratory using primary culture chinchilla middle ear epithelial (CMEE) cells have laid the ground work for the current investigations [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, uncontrolled inflammation due to overproduction of proinflammatory cytokines and chemokines can cause indirect host-mediated tissue damage. Emerging studies revealed that higher-than-normal levels of IL-8 were detected in most middle ear effusions of OM (17,23) and sputum of COPD (27), suggesting that IL-8 contributes to this pathology. This is further supported by an animal model in which direct injection of IL-8 into the murine middle ear induced leukocyte accumulation at that site (13).…”
mentioning
confidence: 99%
“…Histology shows fewer mucus-secreting cells in the middle ear mucosa in serous compared to viscous OME [10]. Mucus contains water, cells, cell debris, high molecular weight compounds (mucins, proteins, and lipids), immunoglobulins, lysozyme, lactoferrin and complement components, antimicrobial peptides, leukotrienes and cytokines [3,10,[28][29][30][31][32]. These chemical defenses ensure that an antimicrobial milieu is constantly present [3].…”
Section: Effusionmentioning
confidence: 99%